Homogeneous gold catalysis beyond assumptions and proposals: characterized intermediates - Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2010)
Gold catalysis is a very active area in the field of catalysis research. New reactions are published every week, amazing changes in the connectivity are often observed, the number of applications in total synthesis is increasing …︁—but what are the mechanisms of these reactions? Sound information can be provided by knowledge about the intermediates of these reactions.
Gesehen am 24.03.2023